2011
DOI: 10.1139/h11-018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2 vitamin D supplementation modalities in newborns: adherence and preference

Abstract: Lack of adherence with vitamin D supplementation is still a risk factor for rickets. In a randomized cross-over design, infants received 400 IU cholecalciferol by dropper (1 mL syrup) or filmstrip. Infant and parent preference scores and adherence were then compared. Forty-three parents of healthy infants preferred the filmstrip (85.4% of parents; 95% confidence interval of 70.1%-93.9%; p < 0.001), a result that was corroborated by higher infant and parental scores and compliance. Ease of administration of sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Interestingly 80% of caregivers reported giving their infants D-Drops ® versus only 16% who supplemented with D-Vi-Sol ® . The reason for the popularity of D-Drops ® may be their ease of administration requiring only a single drop that can be placed on the mother's breast prior to nursing, versus the need to use a dropper to administer D-Vi-Sol ® [25]. …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly 80% of caregivers reported giving their infants D-Drops ® versus only 16% who supplemented with D-Vi-Sol ® . The reason for the popularity of D-Drops ® may be their ease of administration requiring only a single drop that can be placed on the mother's breast prior to nursing, versus the need to use a dropper to administer D-Vi-Sol ® [25]. …”
Section: Discussionmentioning
confidence: 99%
“…Despite the simplicity of the prevention and treatment of vitamin D deficiency, many studies have confirmed poor patient treatment adherence, more so in preventative strategies ( Rodd et al, 2011 ; Grant et al, 2014 ). The option of stoss therapy or single large dose vitamin D treatment to combat the problems associated with treatment adherence has been recommended.…”
Section: Treatment Of Nutritional Ricketsmentioning
confidence: 99%
“…Options include fortification of additional foods, which is very effective and inexpensive (27), or Stoss therapy with large dose oral or intramuscular doses of vitamin D, which remains controversial in paediatrics (1). Ongoing campaigns to alert communities to risks of deficiency and the importance of supplements will be vital; promotion of easy to use preparations has improved uptake in Canada (28). There are lessons to be learned from Turkey and the city of Birmingham, that have implemented successful and inexpensive programs through ongoing education by all health care providers at every visit or patient contact (29,30).…”
Section: Discussionmentioning
confidence: 99%